1996
DOI: 10.1161/01.str.27.7.1200
|View full text |Cite
|
Sign up to set email alerts
|

Complications and Outcome After Acute Stroke

Abstract: Bedside assessment of swallowing is of use in identifying patients at risk of developing complications. The value of routine screening with videofluoroscopy to detect aspiration is questioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
175
1
8

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 601 publications
(198 citation statements)
references
References 13 publications
5
175
1
8
Order By: Relevance
“…Only 12% did not recover and continued to have complaints relating to swallowing. These results were in agreement with other studies that showed that recovery of swallowing occurred over the first few weeks after the event, and that swallowing disorders only remained in a small number of patients 9,10,13,14 . A study using functional magnetic resonance imaging among dysphagia patients showed that among patients who had recovered within a short period of time, cortical maps in the hemisphere not affected by stroke explained this as reorganization in the cortex 5 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Only 12% did not recover and continued to have complaints relating to swallowing. These results were in agreement with other studies that showed that recovery of swallowing occurred over the first few weeks after the event, and that swallowing disorders only remained in a small number of patients 9,10,13,14 . A study using functional magnetic resonance imaging among dysphagia patients showed that among patients who had recovered within a short period of time, cortical maps in the hemisphere not affected by stroke explained this as reorganization in the cortex 5 .…”
Section: Discussionsupporting
confidence: 93%
“…Such cases would be more likely to show abnormalities of swallowing. Our patients were seen at the clinic within 30 days after hospital discharge, which was in accordance with the literature, which shows that swallowing disorders are greatest in severe stroke cases and in the acute phase of stroke 13 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Neverthless, if complemented by videofluorscopic evaluation, the incidence grows to 90%. The explanation for the high incidence observed in this study could be pointed to the fact that dysphagia was registered on different times of the convalescence period.The data reinforces the importance of repeated evaluations made by different professionals of the sttaff involved in acute stroke attendance.KEY WORDS: epidemiology, oropharyngeal dysphagia, stroke.A disfagia é reconhecida como um dos principais fatores de risco para ocorrência de pneumonia aspirativa 1,2 , uma das complicações mais freqüentes dos acidentes vasculares do encéfalo (AVEs), principal causa de morte no Brasil 3 . Barreto 4 chamava a atenção para a freqüência e gravidade de disfagia após AVEs e para a necessidade do pronto reconhecimento e tratamento adequado.…”
unclassified